Utilização de veículos com multi-compartimentos na definição de rotas de recolha de resíduos recicláveis - Oliveira, Adriano Dinis (2015)
The concern about collecting and treating recyclable waste has been growing in Portugal since the 90's. Vehicle routing problems has a key role in companies with the mission to collect and treat waste, since it represents between 66-69 % of the total costs. The goal of this project is to study a routing problem which uses vehicles with multi-compartments. This project was developed using data from Valorsul, a company responsible for collecting waste in the surrounding areas of Lisbon. In this project it is developed a heuristic, cluster-first route-second, and it is made a comparison with the solution used by Valorsul, which uses vehicles with only one compartment. When analysing the results it is seen that the solution found in the study is better than the one used by the company. MCVRP is a problem that has not yet been studied extensively so we recommend a further research in developing heuristics and metaheuristics, but always comparing with the solutions obtained by the classical problem.